(untitled) (Research, Society and Development, 2021)
Several models that seek to explain the learning process have been structured in order to understand aspects related to teaching. These models, called Learning Theories, then serve to change perspectives, as it is known that the way teaching has been conducted is ineffective. With reference to the directions that teaching is taking, as it is out of context with the reality and interest of students, this article seeks to present the Learning Theory structured by Jerome Bruner, in order to address its theoretical foundations, so that they can be used as a support reference for didactic activities and that can enable teaching to achieve positive results. In this way, it is expected to contribute to improving the quality of teaching, especially Science Teaching in Brazilian schools, since in other European countries and the United States, Jerome Bruner’s Theory has already been worked on and disseminated, promoting a focused teaching to the cognitive particularities of each individual.